2023
DOI: 10.1002/jcp.30950
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress promotes sepsis‐induced muscle atrophy via activation of STAT3 and Smad3

Abstract: Endoplasmic reticulum (ER) stress is involved in skeletal muscle atrophy in various conditions, but the role of ER stress in sepsis‐induced muscle atrophy is not well understood. In this study, we conducted experiments in wild‐type (WT) mice and C/EBP homologous protein knockout (CHOP KO) mice to explore the role and mechanism of ER stress in sepsis‐induced muscle atrophy. Cecal ligation and puncture (CLP) was used to establish a mouse model of sepsis. In WT mice, the body weight, muscle mass, and cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The ER stress is a potential factor for muscle mass wasting (Zheng et al., 2023 ). PERK and ATF6 are activated as sensing proteins of ER stress (Hetz, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ER stress is a potential factor for muscle mass wasting (Zheng et al., 2023 ). PERK and ATF6 are activated as sensing proteins of ER stress (Hetz, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that AGEs may disrupt proteostasis and thereby induce skeletal muscle dysfunctions or have a biphasic effect, thereby inhibiting protein degradation for short periods and enhancing it for longer periods. The ER stress is a potential factor for muscle mass wasting (Zheng et al, 2023). PERK and ATF6 are activated as sensing proteins of ER stress (Hetz, 2012).…”
Section: Muthyalaiahmentioning
confidence: 99%
“…In a former research study [16], ER stress is activated and involved in disuse-induced muscle atrophy. Additionally, our previous study [17] reported that ER stress promotes sepsis-induced muscle atrophy. The upregulation of biomarkers of ER stress follows an analogous trend to that of atrophy-related genes, which reveals a correlation between ER stress and sepsis-induced muscle atrophy.…”
Section: Introductionmentioning
confidence: 93%
“…ER stress can also cause impaired muscle protein synthesis, leading to muscle atrophy. There is a strong link between ER stress and muscle atrophy and dysfunction 12,26 . Therefore, reducing ER stress is an effective strategy to improve VIDD.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong link between ER stress and muscle atrophy and dysfunction. 12 , 26 Therefore, reducing ER stress is an effective strategy to improve VIDD.…”
Section: Introductionmentioning
confidence: 99%